Linking Weak and Strong Sustainability Indicators: The Case of Global Warming - Klaus Rennings; Olav Hohmeyer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
The aim of this paper is to describe and discuss the weak and strong sustainability approach of assessing climate change and to show reasonable applications, weaknesses, possible improvements and linkages of both approaches. Main features of ?weak? and ?strong? sustainability approaches are characterized. Damage cost studies of global warming representing weak sustainability indicators are discussed. Further, the examples of the ?inverse scenario? approach of the German Advisory Council on Global Change (WBGU) and the environmental space concept of the Dutch Advisory Council for Research on Nature and Environment (RMNO) are described and discussed for illustrating advantages and weaknesses of strong sustainability indicators. Finally, the integration of damage cost modules into a broader methodological framework of strong sustainability is recommended.
Keywords: 330; weak sustainability; strong sustainability; environmental space; invers scenario; external costs; climate change; global wearming; damage costs; Klimaveränderung; Nachhaltige Entwicklung; Wirtschaftsindikator; Umweltbelastung; Soziale Kosten; Theorie; Deutschland; Niederlande